Proceedings of the Fifth International Conference on Tangible, Embedded, and Embodied Interaction 2010
DOI: 10.1145/1935701.1935723
|View full text |Cite
|
Sign up to set email alerts
|

Supporting embodied exploration of physical concepts in mixed digital and physical interactive settings

Abstract: In this paper findings are presented from a study on how sensor equipped computer game technologies can be used to create tools for educational settings to learn about for example concepts in physics. In a workshop focusing on the concept of gravity, a group of children interacted with an environment consisting of both physical and digital interactive components. We discuss how the mixed digital and physical setting affects the children's coordination and collaboration and their strategies to solve the given a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 12 publications
(5 reference statements)
0
5
0
Order By: Relevance
“…Evaluation is typically used in research projects with a research artefact as the outcome [7,18,27]. Workshops have been acknowledged as a means of testing 'in-the-wild' [87]; its open-ended nature allows for the unexpected to be brought to light.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation is typically used in research projects with a research artefact as the outcome [7,18,27]. Workshops have been acknowledged as a means of testing 'in-the-wild' [87]; its open-ended nature allows for the unexpected to be brought to light.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the created didactical model of simulation is an effective instructional technique. Ahmet et al (2011) explored the possibility of using Nintendo Wii sensors in combination with video games for the purpose of creating the tools for studying the basic concepts in physics. The learning style of 18 Swedish elementary school students was assessed by the questionnaire based on Dunn and Dunn (1978) model.…”
Section: Discussionmentioning
confidence: 99%
“…Virtual reality systems are designed to support multimodal activities such as head and hand movements [6,7] and video capture systems process full body motion [8ś10]. While these and other prototypes continue to be evaluated for how they incorporate gesture and head movements [11,12], support for full body interaction remains elusive.…”
Section: Literature Reviewmentioning
confidence: 99%